Exploring the experiences in mainstream schools with the implementation of the Policy on Screening, Identification, Assessment and Support (2014) - Von Solms, Nastassja (University of the Free State, 2020)
The aim of this qualitative study was to explore the experiences in mainstream schools with the implementation of the Policy on Screening, Identification, Assessment and Support (SIAS policy) of 2014. As I was interested in discovering reality through the experiences of members of the School-Based Support Team (SBST), my study was informed by interpretivism. Premised on interpretivism as my paradigmatic orientation, I focused on the participants’ multiple experiences with interpretations of the SIAS policy. In order to realise the research aim, my study evolved through logically sequenced chapters. Although the chapters are interrelated, each chapter responded to a specific research question and objective, and involved a particular research method. A literature review enabled a conceptual understanding of a global perspective on disability, the international treaties on inclusion and various theories on inclusion. Against my understanding of the medical model of disability, the social model of disability, the theory of full-inclusion and the theory of inclusive special education, I considered how inclusive education is implemented in four countries. I concentrated on two developing countries in the global south, namely Zimbabwe and Lesotho, and two developed countries, namely Finland and Italy. To contextualise the study, I give a brief overview of the trajectory of inclusive education in South Africa. After South Africa became a democracy in 1994, its position on inclusive education shifted from the medical model of disability to the social model of disability. As such, attempts were prompted to reduce the barriers found in society for those with disabilities. This attempt resulted in the enactment of various education policies aimed at the inclusion of all learners in education. A document analysis was undertaken to foreground a policy framework for inclusive education. The framework consists of the Constitution of the Republic of South Africa (1996), the South African Schools Act (1996), the National Education Policy Act (1996), and Education White Paper 6: Building an Inclusive Education and Training System (2001). The commonality in all of these documents is the advancement of inclusion. In drawing on this legislative framework, I was able to position the SIAS policy in relation to the fundamental principles that drive inclusive education in South Africa. In order to explore the experiences in mainstream schools with the implementation of the SIAS policy, I conducted focus group interviews with members of the SBST’s and semi-structured interviews with vice-principals of three primary schools. These schools varied in terms of their quintile categorisation, ranging from quintile level 3 to 5. The findings centred on themes relating to the SIAS process, challenges experienced by the schools and recommendations for a more sufficient implementation of the SIAS process. The findings revealed challenges such as insufficient school readiness, a lack of parental involvement, elongated processes, teacher’s attitudes and inadequate resources. The need to simplify the forms of the SIAS process, and the need for in-service training were brought to the fore. Based on the findings of this study, I made suggestions for improved resources provisioning, skills development for teaching staff who are required to support learners who experience barriers to learning, and the strengthening of relationships between the school and the DBE, and also with parents. In addition to proving some insight in the experiences in mainstream schools with the implementation of the SIAS policy, the study also implicates an existing gap between policy expectations and school realities.
Dissertation (M.Ed. (School of Education Studies))--University of the Free State, 2020
Keywords: Policy on Screening, Identification, Assessment and Support; Interpretivism; Inclusive education; Inclusive special education; Skills development for teaching staff